THE RELEVANCE OF KI HAJAR DEWANTARA'S EDUCATIONAL PHILOSOPHY IN THE NATIONAL EDUCATION CURRICULUM POLICY BASED ON MERDEKA BELAJAR: (A Study at Muhammadiyah Al Mujahidin Senior High School, Wonosari) - Yaqin, Mohammad Nurul; Samad, Muhammad Husni; Sabaruddin, Sabaruddin (TRANSFORMATIONAL LANGUAGE, LITERATURE, AND TECHNOLOGY OVERVIEW IN LEARNING, 2024)
Education policies and curricula in Indonesia are constantly changing.   These changes have a big impact on how learning is done in schools.   Muhammadiyah Al Mujahidin High School in Wonosari is one school that started using the new curriculum.   The author links Ki Hajar Dewantara's educational philosophy with the new curriculum because they are related.   The research focuses on Ki Hajar Dewantara's philosophy, how it is implemented at the school, and its relevance to the National Education Curriculum Policy.   The method used is qualitative research with a descriptive qualitative approach and method, then continued with field research using observation, interview and documentation techniques. Then, for data analysis techniques this research uses data analysis techniques according to Miles and Huberman, namely qualitative data obtained from data reduction, data display, and conclusion drawing/verification. Results and conclusions: Ki Hajar Dewantara's educational philosophy focuses on freedom, namely independence in the sense that education is not dictation but is guidance. Muhammadiyah Al Mujahidin High School has implemented the independent learning curriculum very well and is well received among students and teaching staff, because the learning activity program at Muhammadiyah Al Mujahidin High School is used to carrying out activities that are similar to the system in the independent learning curriculum. The relevance of Ki Hajar Dewantara's educational philosophy to the independent curriculum at Muhammadiyah Al Mujahidin High School is Experience-Based Education, Student-Centered Learning, Character Education, Student Independence, Local Community Involvement, and Inclusivity and Diversity.